Multiple identification of most important waterborne protozoa in surface water used for irrigation purposes by 18S rRNA amplicon-based metagenomics - Moreno-Mesonero, L. (2020)
In this study, we evaluated a NGS-based method as a detection approach to identify simultaneously most important WPPs using 18S rRNA high-throughput sequencing. A set of primers to target the V4 18S rRNA region of WPPs such as Cryptosporidium spp., Giardia sp., Blastocystis sp., Entamoeba spp, Toxoplasma sp. and free-living amoebae (FLA) was designed. In order to optimize PCR conditions before sequencing, both a mock community with a defined composition of representative WPPs and a real water sample inoculated with specific WPPs DNA were prepared. Using the method proposed in this study, we have detected the presence of Giardia intestinalis, Acanthamoeba castellanii, Toxoplasma gondii, Entamoeba histolytica and Blastocystis sp. at species level in real irrigation water samples. Our results showed that untreated surface irrigation water in open fields can provide an important source of WPPs. Therefore, the methodology proposed in this study can establish a basis for an accurate and effective diagnostic of WPPs to provide a better understanding of the risk associated to irrigation water.